2007
DOI: 10.1111/j.1365-2249.2007.03526.x
|View full text |Cite
|
Sign up to set email alerts
|

Immune reconstitution in human immunodeficiency virus type 1-infected children with different virological responses to anti-retroviral therapy

Abstract: SummaryImmune repopulation, despite virological failure, often occurs in children under highly active anti-retroviral therapy (HAART). The aim of this study was to analyse the characteristics of immune repopulation and activation in children with and without virological response to HAART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
61
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 42 publications
7
61
2
Order By: Relevance
“…50 The microbial translocation hypothesis needs further investigation in children where data so far are limited and conflicting. 15,22,38,51 Our data indicate that MT may consist of low levels of multiple organisms resident within the GI tract. Given the increased survival of HIV-infected children on ART, 52,53 investigating the importance of MT in this population and in resource-limited settings is vital for the future rational design of intervention studies.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…50 The microbial translocation hypothesis needs further investigation in children where data so far are limited and conflicting. 15,22,38,51 Our data indicate that MT may consist of low levels of multiple organisms resident within the GI tract. Given the increased survival of HIV-infected children on ART, 52,53 investigating the importance of MT in this population and in resource-limited settings is vital for the future rational design of intervention studies.…”
mentioning
confidence: 72%
“…There has so far been few data generated investigating the question of MT in HIV-infected children, 15,22,38,39 with this being the first study to our knowledge using molecular techniques to identify MT in children in the developed world, and the only one to have successfully sequenced bacterial DNA using conventional and high-throughput techniques. In adult populations standard sequencing has been carried out in only a handful of studies 17,30 and has yielded results compatible with possible contamination such as Serratia spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma LPS was quantified using a chromogenic assay (Limolus Amebocyte Lysate QCL-1000), as previously reported. 16 Levels of IL-6, IL-10, and TNF-alpha were determined in the sera of 94 patients. Cytokines were quantified with Fluorokine MAP Human IL-6 kit, Fluorokine MAP Human TNF-␣/TNFSF2 kit and Fluorokine MAP Human IL-10 kit (R&D Systems) designed for using the Luminex 200 TM , according to manufacturer's instructions.…”
Section: Microbial Translocation and Quantification Of Circulating Cymentioning
confidence: 99%
“…[15][16][17] Studies have recently shown that in HIV and pathogenic simian immunodeficiency virus (SIV) infection microbial products translocate from the lumen of the gastrointestinal (GI) tract, which is both structurally and immunologically damaged during acute phase of infection, into the systemic circulation; these microbial products are bioactive in vivo and contribute to immune activation during the chronic phase of infection. [18][19][20][21][22] However, naturally SIV-infected sooty mangabeys (SM) that do not progress to AIDS or manifest chronic immune activation do not develop microbial translocation. 19 Because Th17 cells are thought to play a central role in antibacterial immunity, particularly at mucosal surfaces, we sought to examine the frequency, phenotype, functionality, antigen specificity, and in vivo infection frequency of Th17 cells in the peripheral blood (PB), GI tract, and broncheoalveolar lavage of HIV-infected and uninfected persons and SIV-infected and uninfected SMs.…”
Section: Introductionmentioning
confidence: 99%